A SURVEY ON HAND GESTURE RECOGNITION FOR DYNAMIC IMAGES - G.Manojkumar; Dayal , Aastha; Shalini, Lingampally (International Journal of Psychosocial Rehabilitation, 2020)
Hand gesture recognition system provides us a natural, user friendly way of interaction with computer. According to WHO, world about 65% people are visually impaired, 5% are deaf and 28% are dumb of all the population. The voice and vision are the major defect for these people. Sign language is the common way to communicated among them but it is not necessary that all physically challenged people can understand. Many people can’t express their feelings to others; they are dependent on sign languages. Problem also arises because of different sign languages; such as American Sign Language, Indian Sign Language, Indo Pakistani Sign Languages, British Sign Languages, Spanish Sign Language and many more; as they don’t know other sign languages. Sign language is composed of different gestures and body movement. This paper provides us various methods and techniques of hand gesture recognition.